Standard and emerging CMR methods for mitral regurgitation quantification. (15th May 2021) - Fidock, Benjamin; Archer, Gareth; Barker, Natasha; Elhawaz, Alaa; Al-Mohammad, Abdallah; Rothman, Alexander; Hose, Rod; Hall, Ian R.; Grech, Ever; Briffa, Norman; Lewis, Nigel; van der Geest, Rob J.; et al.
Abstract: Background: There are several methods to quantify mitral regurgitation (MR) by cardiovascular magnetic resonance (CMR). The interoperability of these methods and their reproducibility remains undetermined. Objective: To determine the agreement and reproducibility of different MR quantification methods by CMR across all aetiologies. Methods: Thirty-five patients with MR were recruited (primary MR = 12, secondary MR = 10 and MVR = 13). Patients underwent CMR, including cines and four-dimensional flow (4D flow). Four methods were evaluated: MRStandard (left ventricular stroke volume - aortic forward flow by phase contrast), MRLVRV (left ventricular stroke volume - right ventricular stroke volume), MRJet (direct jet quantification by 4D flow) and MRMVAV (mitral forward flow by 4D flow - aortic forward flow by 4D flow). For all cases and MR types, 520 MR volumes were recorded by these 4 methods for intra−/inter-observer tests. Results: In primary MR, MRMVAV and MRLVRV were comparable to MRStandard ( P > 0.05). MRJet resulted in significantly higher MR volumes when compared to MRStandard ( P < 0.05) In secondary MR and MVR cases, all methods were comparable. In intra-observer tests, MRMVAV demonstrated least bias with best limits of agreement (bias = −0.1 ml, −8 ml to 7.8 ml, P = 0.9) and best concordance correlation coefficient (CCC = 0.96, P < 0.01). In inter-observer tests, for primary MR and MVR, least bias and highest CCC were observed for MRMVAV . For secondary MR, bias was lowest for MRJet (−0.1 ml, PNS). Conclusion: CMR methods of MR quantification demonstrate agreement in secondary MR and MVR. In primary MR, this was not observed. Across all types of MR, MRMVAV quantification demonstrated the highest reproducibility and consistency. Highlights: In primary mitral regurgitation, direct quantification has significant limitations MRMVAV method is the most consistent method quantification across all groups. All CMR methods are agreeable in secondary and valvular intervention groups